Three‐Dimensional Electrical Structure Beneath the Epicenter Zone and Seismogenic Setting of the 1976 Ms7.8 Tangshan Earthquake, China - Juntao Cai; Xiaobin Chen; Zeyi Dong; Yan Zhan; Zhongyin Liu; Tengfa Cui; Feng Jiang (Geophysical Research Letters)
Abstract Based on magnetotelluric array data and the three‐dimensional (3D) inversion algorithm, we obtain the 3D electrical structure of the 1976 Ms7.8 Tangshan earthquake zone. The seismogenic structure comprised a thick resistive anomaly located east of the Tangshan fault (TSF), a thin resistive belt extending westward, and the TSF zone. A geodynamic model is proposed based on the 3D electrical model and the other research findings. The model indicates that the primary cause of the Tangshan earthquake was the almost EW‐trending horizontal pushing from the west. The local uplift of deep thermal materials on the west side of TSF produces tensile deformation superimposed on the existing shear deformation. The combined effect of these two forces controls the Tangshan earthquake deformation characteristic. Prevailing horizontal pushing from the west and local uplift of hot material may be associated with the Tibet Plateau's eastward escape and the subduction of the Pacific plate.